2019
DOI: 10.1002/ppul.24261
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary findings in infants with cystic fibrosis during the first year of life: Results from the Baby Observational and Nutrition Study (BONUS) cohort study

Abstract: Importance Treatment recommendations for infants with CF standardize care, but most surveillance or treatment guidance of pulmonary manifestations are consensus-based due to sparse evidence. Objective To report observations about pulmonary correlates of growth and other clinical features in infants with CF. Methods We analyzed data from the prospective Baby Observational and Nutrition Study conducted in 28 centers across the US, including clinical features, medications, guardian diaries of respiratory symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Studies that have looked at children up to age 3 report an increased prevalence of abnormal scores in older toddlers, 13 suggesting worsening of disease over time. In the BONUS study, investigators support the recommendation for a more sensitive indicator of lung disease in infants, as higher CXR scores were not seen to occur more frequently in infants colonized with Pseudomonas , 12 a known risk factor for disease progression.…”
Section: Chest Radiographymentioning
confidence: 96%
See 2 more Smart Citations
“…Studies that have looked at children up to age 3 report an increased prevalence of abnormal scores in older toddlers, 13 suggesting worsening of disease over time. In the BONUS study, investigators support the recommendation for a more sensitive indicator of lung disease in infants, as higher CXR scores were not seen to occur more frequently in infants colonized with Pseudomonas , 12 a known risk factor for disease progression.…”
Section: Chest Radiographymentioning
confidence: 96%
“…The Baby Observational and Nutrition Study (BONUS), 11 a prospective multicenter study of 231 infants with CF, has provided a wealth of additional information regarding CXR abnormalities detected in infants 12 . The Wisconsin System, a well‐established CXR scoring system, 13 rates each CXR on a scale of 0 to 100, with higher scores indicating more severe disease, and a cut‐off of less than 5 indicating very mild, and likely reversible, disease.…”
Section: Chest Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1 infants had more pulmonary exacerbations, which drive pulmonary function decline [ 47 , 48 ]. A prospective study of growth in infants with CF diagnosed via NBS showed no association between low weight and hospitalization [49] , though race and ethnicity of participating infants was not reported in the cohort Group 1: infants categorized as Black/African American, American Indian/ Native Alaskan, Asian, and/or other race, and/or Hispanic ethnicity. Group 2: infants categorized as White and not Hispanic.…”
Section: Article In Pressmentioning
confidence: 98%
“…Results: Among 6354 infants, 21% were in Group 1. Group 1 median AFE was 31 days (IQR 19,49) and Group 2 was 22 days (IQR 14,36) (p < .001). Median WFA z-score at 1-2 years was lower in Group 1.…”
mentioning
confidence: 95%